Economic security for a better world - ILO Socio-Economic Security Programme (Geneva International Labor Office, 2004)
Drawing primarily on a special Global Database of national statistical indicators, coupled with a set of People's Security Surveys, covering over 48,000 households in 15 countries, and a set of Enterprise Labour Flexibility and Security Surveys, covering over 10,000 firms in 12 countries, provide a picture of the emerging patterns of economic security across the world.
Part I.
1 Conceptualizing people's security --
2 The liberalization context of insecurity --
Part II.
Monitoring socio-economic security --
3 Income security: The deepening divide --
4 Monitoring income security --
5 Labour market security --
6 Employment security --
7 Work security --
8 Skills security --
9 Job security --
10 Voice representation security --
11 The Economic Security Index --
Part III.
12 Attitudes to economic justice and security --
13 Emerging forms of voice representation security --
14 Seeking income security --
Includes bibliographical references (p. 429-447).
Keywords: Economic conditions; LIVING CONDITIONS; WORKING CONDITIONS; ECONOMIC CONDITIONS; INCOME DISTRIBUTION; SOCIAL SECURITY; EMPLOYMENT SECURITY; DEVELOPING COUNTRIES; DEVELOPED COUNTRIES